Software war stories : case studies in software management - Reifer, Donald J.; IEEE Xplore (Online Service); Wiley (Hoboken, New Jersey : Wiley, 2013)
A comprehensive, practical book on software management that dispels real-world issues through relevant case studiesSoftware managers inevitably will meet obstacles while trying to deliver quality products and provide value to customers, often with tight time restrictions. The result: Software War Stories.This book provides readers with practical advice on how to handle the many issues that can arise as a software project unfolds. It utilizes case studies that focus on what can be done to establish and meet reasonable expectations as they occur in government, industrial, and academic settings. The book also offers important discussions on both traditional and agile methods as well as lean development concepts.Software War Stories:. Covers the basics of management as applied to situations ranging from agile projects to large IT projects with infrastructure problems. Includes coverage of topics ranging from planning, estimating, and organizing to risk and opportunity management. Uses twelve case studies to communicate lessons learned by the author in practice. Offers end-of-chapter exercises, sample solutions, and a blog for providing updates and answers to readers' questionsSoftware War Stories: Case Studies in Software Management mentors practitioners, software engineers, students and more, providing relevant situational examples encountered when managing software projects and organizations.
Exercise: When Trying to Get a Software Project Back on Track, What do You Focus On?Summary of Key Points and Lessons Learned; References; Web Pointers; Chapter 5: Industrial Case: Staff Turnover Having an Impact in Financial Firm; Learning Objectives: Addressing Staffing Issues; Setting the Stage: Understanding the Learning Curve; Fact-Finding; Options, Recommendations, and Reactions While Building a Modern Test Organization; Organization; Project and Process; Product; Recommendations; Outcomes and Lessons Learned While Addressing Test Issues
In Wiley online library
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/22/2015.
Keywords: Software measurement -- Case studies; Electronic books